Spindle Bursts in Neonatal Rat Cerebral Cortex - Jenq-Wei Yang; Vicente Reyes-Puerta; Werner Kilb; Heiko J. Luhmann (Neural Plasticity)
Spontaneous and sensory evoked spindle bursts represent a functional hallmark of the developing cerebral cortex in vitro and in vivo. They have been observed in various neocortical areas of numerous species, including newborn rodents and preterm human infants. Spindle bursts are generated in complex neocortical-subcortical circuits involving in many cases the participation of motor brain regions. Together with early gamma oscillations, spindle bursts synchronize the activity of a local neuronal network organized in a cortical column. Disturbances in spindle burst activity during corticogenesis may contribute to disorders in cortical architecture and in the activity-dependent control of programmed cell death. In this review we discuss (i) the functional properties of spindle bursts, (ii) the mechanisms underlying their generation, (iii) the synchronous patterns and cortical networks associated with spindle bursts, and (iv) the physiological and pathophysiological role of spindle bursts during early cortical development.